Correlation of biological activities of bark and leaves of Terminalia arjuna collected from different geographical regions of Himachal Pradesh, India. (February 2023) - Kumar, Vikas; Sharma, Nitin; Sourirajan, Anuradha; Khosla, Prem Kumar; Dev, Kamal
Abstract: Terminalia arjuna (Roxb) Wight & Arnot, belonging to the Combretaceae family, is one of the beneficial medicinal trees in the indigenous system. The present study aimed to compare phytocompounds and biological activities in the bark and leaves of T. arjuna collected from different regions of Himachal Pradesh. Quantitative analysis of total phenols (TPCs) and flavonoids (TFCs) revealed that the extracts from the bark of T. arjuna showed significant variations in TPC and TFC, whereas the extracts from the leaves of the different accessions had similar content. The bark extracts exerted antibacterial efficacy against all microorganisms tested, although the leaf extracts induced greater growth inhibition of Staphylococcus aureus . The data of the antioxidant tests DPPH, FRAP, and NO confirmed the greater activity of the bark extracts, also highlighting that the extracts from samples collected in the Kangra region were particularly responsive to the tests conducted. This is to underline that potentially in the Kangra region the environmental conditions are suitable for a modulation of the phytochemical content which is reflected in an increase in the biological activity of the bark and leaves of T. arjuna. Highlights: Terminalia arjuna accessions were explored for phenolic and flavonoid content. Bark and leaf extracts were screened for antibacterial and antioxidant activity. Samples of the Kangra region showed higher bioactivity than those from other regions. The Kangra region of Himachal Pradesh can be used for the mass propagation of T. arjuna.